2022
DOI: 10.1017/aaq.2021.141
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Paleoindian Diet Breadth: Paleoethnobotany of Connley Cave 5, Oregon, USA

Abstract: Paleoethnobotanical perspectives are essential for understanding past lifeways yet continue to be underrepresented in Paleoindian research. We present new archaeobotanical and radiocarbon data from combustion features within stratified cultural components at Connley Caves, Oregon, that reaffirm the inclusion of plants in the diet of Paleoindian groups. Botanical remains from three features in Connley Cave 5 show that people foraged for diverse dryland taxa and a narrow range of wetland plants during the summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…55,88 This is the pattern evident in the archaeological records of both late Pleistocene Eurasia and early Holocene North America where so-called Archaic populationsdescended from the late Pleistocene/early Holocene mobile hunters discussed above and defined partly by their relative sedentism-had much broader diets including a range of previously-ignored small game and plants. 8,9,89 In late Pleistocene Eurasia, the pattern is attributed to establishment of sex-specific subsistence labor, 60 a hypothesis usefully extended to the North American Archaic.…”
Section: Implications Of Digesta Consumption: the North American "Arc...mentioning
confidence: 99%
See 1 more Smart Citation
“…55,88 This is the pattern evident in the archaeological records of both late Pleistocene Eurasia and early Holocene North America where so-called Archaic populationsdescended from the late Pleistocene/early Holocene mobile hunters discussed above and defined partly by their relative sedentism-had much broader diets including a range of previously-ignored small game and plants. 8,9,89 In late Pleistocene Eurasia, the pattern is attributed to establishment of sex-specific subsistence labor, 60 a hypothesis usefully extended to the North American Archaic.…”
Section: Implications Of Digesta Consumption: the North American "Arc...mentioning
confidence: 99%
“…When group size exceeds the level at which dietary needs can reliably be met through large‐bodied herbivores and their digesta, groups of optimizing foragers should reduce their day‐to‐day mobility (become more sedentary) and encamp near reliable sources of carbohydrates, sending out logistical hunting parties as necessary 55,88 . This is the pattern evident in the archaeological records of both late Pleistocene Eurasia and early Holocene North America where so‐called Archaic populations—descended from the late Pleistocene/early Holocene mobile hunters discussed above and defined partly by their relative sedentism—had much broader diets including a range of previously‐ignored small game and plants 8,9,89 . In late Pleistocene Eurasia, the pattern is attributed to establishment of sex‐specific subsistence labor, 60 a hypothesis usefully extended to the North American Archaic.…”
Section: Implications Of Digesta Consumption: the North American “Arc...mentioning
confidence: 99%
“…Many postglacial pollen records recovered from within the NGB have been studied at mid- to high-elevation sites, as low-elevation sites containing undisturbed sedimentary sequences that span the Holocene are uncommon (Cohen et al, 2000). The few low-elevation pollen records that do exist reveal the ubiquitous presence of xeric shrub–steppe vegetation since the last glacial maximum (Mehringer, 1987; Wigand, 1987; Wigand and Rhode, 2002; Mensing et al, 2013; Beck et al, 2018; Kennedy, 2018; McDonough et al, 2022). However, wetlands are embedded within this xeric landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Archaeological investigations of caves and rock shelters occasionally yield preserved mammalian coprolites, offering opportunities to gain information about the diet and health of animals and to make inferences about past climates and environments (Bryant, 1974; Hofreiter et al, 2000; Carrión et al, 2001; Gilbert et al, 2008; Riley, 2008; Shillito et al, 2011; Wood and Wilmshurst, 2012, 2016; Beck et al, 2018, 2020; Blong et al, 2020). Coprolite studies have been an important component of Great Basin archaeological research since the early twentieth century (Loud and Harrington, 1929; Heizer, 1969; Heizer et al, 1970; Kelso, 1971; Thomas et al, 1983) and have since greatly expanded our understanding of past human behaviors and health (Jenkins et al, 2012, 2013; Dexter and Saban, 2014; Beck et al, 2018; Kennedy, 2018; McDonough, 2019; Blong et al, 2020; McDonough et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, researchers have increasingly turned their attention to previously excavated sites. In some cases, such as the Paisley Caves (Jenkins et al 2012) and Connley Caves (Jenkins et al 2017; McDonough et al 2022), these efforts have changed our understanding of the peopling of the Great Basin. In others, such as Fort Rock Cave (Connolly et al 2017), renewed work has shown that some sites are irreparably damaged.…”
mentioning
confidence: 99%